On the criteria for determining international phraseological units - Novogran, Yulia V. (Journal of the Belarusian State University. Philology, 2021)
The aim of the article is to analyze and clarify the criteria available in the scientific literature for determining the internationality of phraseological units. The relevance of this research is substantiated, caused by the lack of development of international phraseology in linguistics and in German studies, as well as in the framework of English-Russian and English-Belarusian phraseological comparative studies. The criteria for internationality of phraseological units proposed by various authors are considered, and their own point of view on this issue is expressed. The criterion of the international phraseological units common expression plan in different languages is established to be detected only when borrowed in the original form. In most cases international phraseological units are distributed by the method of calquing. The criterion of the common origins of international phraseological units is argued to be effective only for borrowed phraseological units. International phraseological units are noted to receive additional meanings in national languages, thus demonstrating the processes of development of phraseological polysemy. It is determined that the internationality of a phraseological unit is confirmed by its presence in at least three languages of three language groups belonging to the same or different language families. Some criteria for determining international phraseology are emphasized to be not mandatory. The practical value of the work consists in the possibility to use its results and factual material for the theory of comparative studies, in the preparation of dictionaries and reference books, in the practice of interlingual translation in language teaching and linguistics.
Keywords: international phraseology; borrowing; calculation; criteria for internationality; form of phraseological units; phraseological semantics; phraseological sources; language group; language family